An update on the occurrence of flies (Diptera: Muscidae, Calliphoridae) and sucking lice (Phthiraptera: Anoplura) of veterinary importance in Malta: First record of Lucilia cuprina and Linognathus africanus - Hornok, Sándor; Cini Bruno, Andrea M.; Takács, Nóra; Keve, Gergő; Sándor, Attila D.; Kontschán, Jenő (Frontiers in Veterinary Science, 2023)
To obtain new data on the species diversity, host-associations and spatio-temporal occurrence of flies and blood-sucking lice of veterinary importance in Malta, ectoparasites were collected at cattle, sheep and goat farms, near pigs and dogs, as well as in two places in the absence of domestic animals. The species were identified morphologically, but voucher specimens were also analyzed with molecular-phylogenetic methods following DNA extraction. Altogether 3095 flies (Diptera: Muscidae, Calliphoridae) were collected at farms and kennels near domestic animals, as well as 37 blowflies (Calliphoridae) in rural and urban areas without animals nearby. Regarding Muscidae, the great majority of flies (n = 3084) were identified as the common housefly (Musca domestica). Eight flies represented the stable fly (Stomoxys calcitrans). Three blowflies associated with dogs and small ruminants belonged to Lucilia cuprina. By contrast, all 37 blowflies collected without domestic animals nearby, were identified as L. sericata. In addition, 22 sucking lice were collected from goats, and all belonged to Linognathus africanus. Molecular identification of 28 flies and four lice confirmed the above species. Considering the sex ratio of M. domestica among samples collected randomly at cattle farms, females predominated in the whole study period, but the abundance of males increased significantly towards the autumn. Stomoxys calcitrans was associated with cattle and dogs, whereas L. cuprina was found near small ruminants and dogs. To our knowledge, this is the first study including the molecular analysis of flies and lice of veterinary-medical importance from Malta. The most important finding of this study is the first evidence for the autochthonous occurrence of L. cuprina in Malta. The exclusive presence of L. cuprina at animal-keeping facilities in rural areas and association of L. sericata with urban areas void of livestock might reflect similar habitat preference of these species in Malta to what was reported in South Africa. Based on the sucking-louse burden in the examined goat herds, the situation in Malta was similar to northern Africa where the exclusive presence of L. africanus was reported, unlike towards the north in the Mediterranean Basin where populations of this species are mixed with L. stenopsis.